Phantom tumour of the lung in a patient with renal failure misdiagnosed as chest infection - Althomali, Sarah Ali (BMJ Publishing Group, 2014)
Phantom or vanishing tumour of the lung is a rare finding on chest radiographs that has been reported secondary to heart failure or chronic kidney disease. It has been described as an interlobular effusion of the transverse or oblique fissure of the right lung. Although it is uncommon, it should always be considered as a differential diagnosis for a radiographic opacity of the right-middle lung zone because it can be easily mistaken for a lung mass or infiltration. We herein present a case involving a patient with chronic kidney disease and a radiographic opacity of the right-middle lung that was diagnosed as a chest infection. The patient did not respond to various antibiotics and showed a poor response to diuretics, the standard treatment for phantom tumour. However, the patient markedly improved after dialysis, and the radiographic chest opacity disappeared.